Delta insulin-like growth factor binding protein-1 (ΔIGFBP-1): a marker of hepatic insulin resistance?. (March 2014) - Borai, Anwar; Livingstone, Callum; Heald, Adrian H; Oyindamola, Yusuf; Ferns, Gordon
Background: Insulin-like growth factor binding protein-1 (IGFBP-1) is a hepatically synthesised protein which can be used as a marker of insulin resistance. We hypothesised that the fall in serum IGFBP-1 at 2 h following a glucose load ( Δ IGFBP-10–2h ) would be a more robust measure of hepatic insulin resistance than a fasting level alone. Methods: All subjects had a standard 75 g oral GTT including IGFBP-1 and insulin measurement to enable calculation of Δ IGFBP-10–2h, ΔInsulin0–2h, and insulin sensitivity indices. At a second visit, subjects had a frequently sampled intravenous glucose tolerance test (FSIVGTT) in order to determine the insulin sensitivity index, Si. Results: Twenty-two individuals had normal glucose tolerance (NGT) and 9 impaired fasting glucose (IFG). Δ IGFBP-10–2h correlated with Si in total subjects ( r  = 0.49, p  = 0.005) and NGT subjects ( r  = 0.50, p  = 0.02) but not in IFG subjects ( r  = 0.43, p  = 0.24). ΔInsulin0–2h / Δ IGFBP-10–2h correlated significantly with Si in total subjects ( r  = −0.68, p  < 0.001) and in NGT subjects ( r  = −0.57, p  = 0.005). Multivariate analysis was fitted using different models while keeping other explanatory variables constant. The fasting IGFBP-1 model was a better predictor of Si ( β  = 0.431, p  < 0.0001) than the Δ Insulin0–2h / Δ IGFBP10–2h model ( β  = −0.185, p  = 0.004). Conclusions: The dynamic indices Δ IGFBP-10–2h and ΔInsulin0–2h / Δ IGFBP-10–2h appear suitable markers of (hepatic) insulin resistance with potential clinical utility.